2018
DOI: 10.1371/journal.pone.0199868
|View full text |Cite
|
Sign up to set email alerts
|

Direct archaeological evidence for Southwestern Amazonia as an early plant domestication and food production centre

Abstract: Southwestern Amazonia is considered an early centre of plant domestication in the New World, but most of the evidence for this hypothesis comes from genetic data since systematic archaeological fieldwork in the area is recent. This paper provides first-hand archaeobotanical evidence of food production from early and middle Holocene (ca. 9,000–5000 cal. BP) deposits at Teotonio, an open-air site located on a 40 m-high bluff on the south bank of the Madeira river. Such evidence includes the presence of local and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1
64

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(165 citation statements)
references
References 59 publications
4
96
1
64
Order By: Relevance
“…The trend of change values, and the overall fluctuations in palm abundance (magnitude of change values), were significantly higher at Amacayacu compared with the other forest plots, and nearly reached levels documented at an excavated archaeological site in the Teotônio region of Brazil (Figures and ). In contrast to Amacayacu, however, the Teotônio site has been occupied for 2,000 years, and contains evidence of pottery, soil modifications, recurrent fires, maize cultivation, and palm cultivation (Almeida & Neves, ; McMichael et al, ; Watling et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend of change values, and the overall fluctuations in palm abundance (magnitude of change values), were significantly higher at Amacayacu compared with the other forest plots, and nearly reached levels documented at an excavated archaeological site in the Teotônio region of Brazil (Figures and ). In contrast to Amacayacu, however, the Teotônio site has been occupied for 2,000 years, and contains evidence of pottery, soil modifications, recurrent fires, maize cultivation, and palm cultivation (Almeida & Neves, ; McMichael et al, ; Watling et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 6). In contrast to Amacayacu, however, the Teotônio site has been occupied for 2,000 years, and contains evidence of pottery, soil modifications, recurrent fires, maize cultivation, and palm cultivation (Almeida & Neves, 2014;McMichael et al, 2015;Watling et al, 2018).…”
Section: The History Of Amacayacumentioning
confidence: 99%
“…Invasive plant species are usually divided in two groups according to time of their residence time: archaeophytes brought in up to 1500 AD, and neophytes brought in after this date (Kowarik 1995). Pyšek et al (2005) The origin of P. corethrurus may be related to anthropogenic soil formation ("terras mulatas" and "terras pretas") and the domestication of manioc (bitter and sweet) and peach palm staple food that facilitated sedentary lifestyles in the Amazon region (Lodge 1993;Glaser et al 2000;Arroyo-Kalin 2010;Clement et al 2015;Watling et al 2018;Levis et al 2018), and has evolved to the point that we cannot recognize their wild predecessors, as evidenced by the recent designation of the P. corethrurus neotype from an anthropogenic environment (Müller 1857;James et al 2019), and by the ambiguity used for assigning its place of origin (Righi 1984;Dupont et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to weeds (Willcox 2012;Vigueira et al 2013;Fuller and Stevens 2017;Mercuri et al 2018), it can be suggested that P. corethrurus and B. pearsei have shifted their preference from their natural habitat to agricultural environments, spreading geographically beyond their place of origin, and are currently key elements of agricultural environments. The presence of P. corethrurus and B. pearsei is associated with the development of pre-Columbian cultivation techniques in the Amazon (Clement et al 2015;Levis et al 2018;Boivin et al 2016;Watling et al 2018) and Maya (Ford and Nigh 2009;McNeil 2012;Boivin et al 2016) regions, respectively; for example, it is believed that P. corethrurus facilitated the formation of fertile soils in the Amazon area named "Terra Preta do Indo" (Glaser et al 2000;Ponge 2006). Both species have adapted to niches that emerged from agriculture (Laland et al 199), but contrast regarding the intensification of agricultural land use and/or the diversion of each from natural habitats (anthropic manipulation of soil).…”
mentioning
confidence: 99%
“…ADE formation in IR was estimated to have begun ~1,050 -950 years BP 56 and at BT ~530-450 years BP 57 . At PV, ADE formation began much earlier (~6500 years BP) 8 .…”
Section: One Of the Of In Bt Was At The Embrapa Amazônia Oriental Belmentioning
confidence: 99%